Kajian Sosiologis Pungutan Tapera Terhadap Buruh - Siswahyudi, Siswahyudi; Arifin, Sada; Faizal, Sarman; Yuliana, Risma; Lubis, Ahmad Halim; Rahdar, A. Habib Amanatullah (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2024)
This article examines the impact of the Public Housing Savings Program (Tapera) on Indonesian workers from both legal and social perspectives. The program mandates a 3% salary deduction, shared between employees and employers. However, the policy has faced significant criticism for increasing financial burdens on workers, particularly during challenging economic conditions. The study employs a normative legal approach to analyze relevant regulations and assess the social impact of its implementation. The findings indicate that, while Tapera aims to improve workers' access to housing, it imposes additional financial strains. Furthermore, the lack of worker participation in the policy-making process exacerbates dissatisfaction. To address these issues, it is recommended that the government review the Tapera policy with active involvement from workers and labor unions. Alternative funding mechanisms, such as subsidies from the state budget or lighter installment schemes, should also be considered. A more inclusive and equitable approach could not only enhance the program's effectiveness but also foster stronger relationships between workers, the government, and employers, thereby achieving a better balance in its implementation.